Surgical Management of Giant Intrapericardial Teratoma Encasing the Coronary Artery. Issue 1 (January 2022) - Minocha, Prashant; Hodzic, Emina; Sharma, Madhu; Bhatla, Puneet; Nielsen, James; Ramirez, Michelle; Magid, Margret; Fisher, Jason C.; Mosca, Ralph; Kumar, TK Susheel
Intrapericardial teratomas are rare, predominantly benign tumors that warrant surgical resection in the neonatal period because of their potential detrimental effects on the cardiorespiratory system. Surgical resection can be a challenge when the tumor encases and obscures a coronary artery. Adherence to certain operative principles is necessary to achieve successful outcomes.